If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6m + -1(31m + -18) = 12(m + -1) + 3m Reorder the terms: 6m + -1(-18 + 31m) = 12(m + -1) + 3m 6m + (-18 * -1 + 31m * -1) = 12(m + -1) + 3m 6m + (18 + -31m) = 12(m + -1) + 3m Reorder the terms: 18 + 6m + -31m = 12(m + -1) + 3m Combine like terms: 6m + -31m = -25m 18 + -25m = 12(m + -1) + 3m Reorder the terms: 18 + -25m = 12(-1 + m) + 3m 18 + -25m = (-1 * 12 + m * 12) + 3m 18 + -25m = (-12 + 12m) + 3m Combine like terms: 12m + 3m = 15m 18 + -25m = -12 + 15m Solving 18 + -25m = -12 + 15m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-15m' to each side of the equation. 18 + -25m + -15m = -12 + 15m + -15m Combine like terms: -25m + -15m = -40m 18 + -40m = -12 + 15m + -15m Combine like terms: 15m + -15m = 0 18 + -40m = -12 + 0 18 + -40m = -12 Add '-18' to each side of the equation. 18 + -18 + -40m = -12 + -18 Combine like terms: 18 + -18 = 0 0 + -40m = -12 + -18 -40m = -12 + -18 Combine like terms: -12 + -18 = -30 -40m = -30 Divide each side by '-40'. m = 0.75 Simplifying m = 0.75
| y=8-(1/2)x | | 160x^2-250=0 | | -3c^2+4c-4= | | h=25433(9.5)+28.465 | | 6x+8-4x=20 | | 4(k-2)-6=3k-(2k-3) | | m+m+18=31 | | 243g^2+54g+3=0 | | 61*ln(y)=13 | | 4/3p=9/8 | | 5(2x-6)=25 | | 2(p+9)= | | 4x-3y+z=4 | | 4x+3(2-3x)=40 | | 3x=5+2(3+1x) | | 3(x+3)-3=7(x+1)-4x | | x^3+2x^2+x= | | (x-1)(-6x+6)= | | 7x-5(x+1)+9=19 | | -16.49(4)+5.2= | | ln(5x-13)=4 | | y(2y-8)=0 | | 3(7Y)= | | 5.4(3+2x)-4.2=12 | | 5(x-1)+3(2x-1)=3 | | 4.17x+0.94=3.7x | | 1.7(-9.7x+6)-5= | | 0.1x+0.3= | | 6x-5-1+2x-4x=66 | | 7x-8x+x-5x= | | F=(1.8*-5)+32 | | 32x=456 |